Students' Perceptions of the Use of Artificial Intelligence in Discussion Forum Evaluation on Massive Open Online Courses Platform - Jaka Warsihna; Zulmi Ramdani; Heri Kurniawan; Zulfikri Zulfikri; Fauzy Rahman Kosasih; Mudayat Mudayat; Ahmad Syaikhu (Postgraduate, University of Mataram, 2026)
This study explores university students' perceptions of the use of Artificial Intelligence (AI) in evaluating discussion activities within Massive Open Online Courses (MOOCs). Using a quantitative cross-sectional survey, data were collected from 112 undergraduate students who had participated in AI-assisted discussion forums across four MOOCs. Descriptive statistics were used to analyze students' perceptions of MOOCs and AI-assisted evaluation, followed by inferential tests to examine differences across demographic variables. Findings indicate that students hold generally positive perceptions of MOOCs, particularly regarding their flexibility, ease of use, and structured learning design. Students also evaluated discussion forums as relevant, understandable, and motivating. Although students showed moderate acceptance of AI involvement in evaluation, ethical concerns remained evident. Inferential analysis showed no significant differences in perceptions across most demographic variables, with the exception of employment status, which influenced perceptions of AI-assisted evaluation. The study highlights the need for ethical, transparent, and pedagogically aligned implementation of AI in online learning assessment